TRANSFORMASI FILOSOFI NITENI, NIROKKE, NAMBAHI DALAM MENDESAIN INOVASI PEMBELAJARAN INTERAKTIF GENERASI ALFA - Charissa Muthia Wibowo; Jesy Marwana; Ignatius Ario Sumbogo; Aulia Sandra Maudina; Naysila Eka Julianti; Dara Salsabila Rianti (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The development of the digital era in the world of education demands a learning ecosystem that is not only interactive and cutting-edge, but also remains rooted in local wisdom. The main problem in this research is the challenge of 21st-century education where digital technology penetration often does not correlate with the depth of cognitive processes and local values, necessitating a strong methodological framework to bridge technological sophistication with learning effectiveness. This research aims to design interactive learning innovations for Alpha Generation, who are known to be active and tech-savvy, by transforming Javanese philosophy from Ki Hadjar Dewantara's thoughts, namely Niteni, Nirokke, and Nambahi, into modern learning that aligns with the current "nature of the times" (kodrat zaman). The research method used is Systematic Literature Review (SLR) by deeply examining relevant literature from national and international databases and other journal articles discussing Ki Hadjar Dewantara's thoughts, the Kurikulum Merdeka, and deep learning approaches at the elementary school level. The review results show that the transformation of Niteni is realized through critical observation features, Nirokke through procedural imitation in interactive simulations, and Nambahi as a space for digital creative modification. This integration is proven to create meaningful learning experiences that are in harmony with the "nature of the times" of Generation Alpha without losing cultural roots. This research emphasizes the importance of a learning flow that provides space for independent exploration alongside technical instruction.